Multilateral Debt Relief Initiative : A First Assessment of Eligible Countries--Supplemental Information. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This supplement summarizes new information available to staff since the issuance of The Multilateral Debt Relief Initiative: A First Assessment of Eligible Countries (December 8, 2005). It focuses on the six members (Ethiopia, Madagascar, Mauritania, Nicaragua, Rwanda, and Senegal) for which staff recommends that remedial actions be taken before the Board determines whether they qualify for debt relief from the Fund under the Multilateral Debt Relief Initiative.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Article IV Consultation; MDRI Qualification To The Board; PP; Madagascar; Nicaragua